2002
DOI: 10.1097/00002030-200211220-00009
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance protein 2 (MRP2) transports HIV protease inhibitors, and transport can be enhanced by other drugs

Abstract: Human MRP2 actively transports several HPI and could, based on its known and assumed tissue distribution, therefore reduce HPI oral bioavailability. It may also limit brain and fetal penetration of these drugs and increase their hepatobiliary, intestinal and renal clearance. MRP2 function and enhancement of its activity could adversely affect the therapeutic efficacy, including the pharmacological sanctuary penetration, of HPI. In vivo inhibition of MRP2 function might, therefore, improve HIV/AIDS therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
155
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(166 citation statements)
references
References 30 publications
6
155
2
3
Order By: Relevance
“…When present in epithelial cells, this protein is found primarily in the basolateral membrane (Hipfner et al, 1999). However, it has been reported that MRP1 does not mediate substantial polarized transport of PIs in MDCKII-MRP1 cells (Huisman et al, 2002). In contrast to MRP1, MRP2 is localized on the apical membrane of several epithelia.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…When present in epithelial cells, this protein is found primarily in the basolateral membrane (Hipfner et al, 1999). However, it has been reported that MRP1 does not mediate substantial polarized transport of PIs in MDCKII-MRP1 cells (Huisman et al, 2002). In contrast to MRP1, MRP2 is localized on the apical membrane of several epithelia.…”
Section: Introductionmentioning
confidence: 97%
“…Functionally it is similar to P-gp mediated elimination of toxic compounds in gut and placenta (Kruh and Belinsky, 2003). It has been fairly established that MRP2 effluxes PIs (Huisman et al, 2002;Williams et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the liver, Mrp2 is a canalicular transporter involved in the biliary excretion of many endogenous and exogenous metabolites, including leukotrienes and bilirubin, and many drugs, such as protease inhibitors. [1][2][3] Mrp3 and Mrp4 are high-capacity, low-affinity basolateral transporters that are highly inducible. These hepatoprotective transporters export conjugated bile acids, bilirubin, and other substrates from hepatocytes back into the bloodstream for renal excretion.…”
mentioning
confidence: 99%